Effect of Changes in Cooling Media and Temperature on Steel Hardness - Khalid, Anhar; Heka, Akbar Ela; Fitria, Fitria (MultiTech Publisher, 2024)
The hardness test is one method to determine the effect of heat or cold treatment on the material. This research uses experimental methods. This research uses a type of quantitative research, namely clearly explaining the results of experiments in workshops on test objects, then analyzing the data using numbers. The results of testing using the Vickers method by taking 12 specimens and taking 3 penetrations can be concluded that changes in the structure of the material that has been heat treated results in the structure of the material becoming harder compared to that which has not received treatment.